تعليم اللغة العربية على أساس الذكاءات المتعددة بمؤسسة الدورية مركز العربية بباري كديري - Admi, Letty Maulida (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
The purpose this research is to describe Arabic learning based on linguistic intelligence, use of methods on kinesthetic intelligence, and use media on visual and musical intelligence in learning Arabic in